The Integration of Audiobooks and Read-Aloud Strategies as an Innovation in Indonesian Language Learning to Enhance the Listening and Speaking Skills of First-Grade Elementary School Students - Mawarni Sianipar; Wigati Yektiningtyas; Onny Mentang Lumintang; Budi Rahayu (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Listening and speaking skills are fundamental language competencies that must be developed in the early years of elementary education because they serve as the foundation for literacy development and effective communication. However, many first-grade students experience difficulties in understanding oral information and expressing ideas verbally during classroom learning. This study aimed to examine the effect of integrating audio books and the read-aloud method on the listening and speaking skills of first-grade elementary school students. The study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The participants consisted of 60 first-grade students from SD Negeri 3 Mimika Baru, Indonesia, divided into an experimental group (30 students) and a control group (30 students). Data were collected through listening comprehension tests and speaking performance assessment rubrics. The data were analyzed using descriptive statistics, normalized gain (N-Gain), and Independent Samples t-test. The results revealed that students in the experimental group demonstrated significantly higher improvements in both listening and speaking skills compared to those in the control group. The experimental group achieved an N-Gain of 0.61 for listening skills and 0.60 for speaking skills, while the control group obtained an N-Gain of only 0.24 for both variables. Furthermore, the t-test results showed significant differences between the two groups in listening skills (t = 8.72, p < 0.05) and speaking skills (t = 8.49, p < 0.05). These findings indicate that the integration of audio books and the read-aloud method is effective in enhancing elementary students’ listening and speaking abilities and can serve as an innovative instructional strategy in language learning.